European Nordic Countries Stock Market Listed Companies’: Factor and Cluster Analysis Approach - Aija Pilvere-Javorska; Irina Pilvere (Emerging Science Journal, 2020)
Public financial markets are crucial in the access to the funding and as a platform for investments to the investors in today’s world. Nordic European Union countries such as Sweden, Finland and Denmark are considered to have advanced and well-developed stock markets, while neighboring three Baltic States have rather small stock market. Backbone of the stock market are there listed companies. In this analysis authors attempt to analyze 510 Nordic countries listed companies’ absolute value indicators using factor and cluster analysis and to compare results with similar analysis of the Baltic States. Factor and cluster analysis revealed the homogeneity of Nordic countries stock market listed companies’ absolute values, authors obtained three complex factors, explaining 89% of dispersion within the indicators, which in turn resulted in being able to obtain the portrait of Nordic States stock market listed company. Similar results were obtained for Baltic States listed companies, though on different scale. Authors have not seen as detailed analysis of Nordic Stock market on the level of listed companies financial statement analysis. Time period covered in this research of the financials are from 2004 to 2018. The analysis could be beneficial for other researchers focusing on the Nordic region stock market companies and also to the policy makers in the Baltic States, how the neighboring well-developed countries indicators could be interpreted and obtained results used for the enhancement of Baltic States stock market. Doi: 10.28991/esj-2020-01244 Full Text: PDF